Paraguay : Staff Report for the 2001 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2001)
Adverse terms-of-trade developments and an unfavorable external environment have contributed to Paraguay's lackluster economic performance. Executive Directors observed the fiscal slippages, weaknesses in national accounts calculations, the statistical coverage of public enterprise operations and external tariffs, and stressed the need to tighten monetary and fiscal stances, and accelerate structural reforms. They welcomed the new strategy under the staff-monitored program, the improvement in the balance of payments, money, the central government's finances, and the country's progress toward meeting the General Data Dissemination Standard.